2011
DOI: 10.1007/s10633-011-9298-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological studies in newly onset type 2 diabetes without visible vascular retinopathy

Abstract: The purpose of this study was to investigate the early alterations of retinal function, assessed with electrophysiology, in newly onset type 2 diabetes patients without vascular retinopathy. Seventeen patients with newly diagnosed type 2 diabetes (duration 7±3 months), without any vascular retinopathy in fundus photographs, were examined with full-field electroretinogram (ERG) and multifocal ERG (mfERG). The results were compared with those of age-matched subjects without diabetes. In the dark-adapted full-fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 23 publications
3
45
0
Order By: Relevance
“…The finding of higher than normal ERG amplitudes during the first year of the study is consistent with other studies of the earliest stages of non-proliferative diabetic retinopathy [24,25]. It also supports the theory that hyperglycemia can lead to a hypermetabolic state in the retina [26].…”
Section: Discussionsupporting
confidence: 91%
“…The finding of higher than normal ERG amplitudes during the first year of the study is consistent with other studies of the earliest stages of non-proliferative diabetic retinopathy [24,25]. It also supports the theory that hyperglycemia can lead to a hypermetabolic state in the retina [26].…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, blood-retinal barrier (BRB) breakdown as the result of VEGF upregulation produced by glutamate-induced excitotoxicity has been well documented [9], [11], [12], and a cross-talk between neurodegeneration and vasoregression has been reported [10], [13]. In addition, the impairment of neurovascular coupling which can be detected in diabetic patients without structural abnormalities [32], [33] seems primarily mediated by ganglion cell damage [34]. Finally, it has been shown that a delayed multifocal ERG implicit time predicts the development of early microvascular abnormalities [29], [35][37].…”
Section: Discussionmentioning
confidence: 99%
“…Testing took place in a room with no background light, which has been shown to influence detection of STDR. 18 The sensor strips were disposed of to avoid rescreening of other patients using the used strips. The calibration phase followed prior reports with this device.…”
Section: Methodsmentioning
confidence: 99%